Can AI-Generated Feedback Overshadow Teachers’ Existence? - Rizki Azizah; Agus Wijayanto; Malikatul Laila (Dinasti Publisher, 2025)
AI-generated feedback is expected to be exploited for enhancing learners’ speaking skills and maintaining learners’ emotional state. The magical power might overshadow teachers’ feedback, as well. For further investigating learners’ perception of AI-generated feedback compared to teachers’ feedback in fostering learners’ speaking skills and maintaining emotional state, this study employed a mix-method. Data were collected through a 15-item questionnaire and semi-structured interviews with Grade XI students at Budi Utomo Senior High School. The questionnaire examined the intensity of feedback reception, learners’ preferences for feedback providers in improving speaking skills (lexis, stressed word patterns, intonation, fluency, grammar, communicative functions, and physical paralinguistic features), and the emotional impact of feedback (self-esteem, motivation, and anxiety). Interviews, conducted via WhatsApp voice notes for flexibility, provided deeper insights into learners' experiences with both feedback types. Thematic analysis revealed that learners perceived AI-generated feedback as beneficial for improving specific aspects of speaking, particularly pronunciation and fluency, while teacher feedback was valued for its personalized and interactive nature. Emotional responses varied, with AI-generated feedback fostering self-directed learning but sometimes lacking the motivational support provided by teachers. The study highlights the complementary roles of AI and teacher feedback in fostering speaking skill development and emotional engagement. These findings contribute to the ongoing discourse on AI in language education and provide implications for optimizing feedback strategies in EFL classrooms.